PARTISIPASI PEMUDA KARANG TARUNA MAHARDIKA DALAM PEMBANGUNAN DESA JUBEL KIDUL KECAMATAN SUGIO KABUPATEN LAMONGAN: PEMUDA DAN MENTAL INTERPRENEURSHIP - Fadli, Ricki (Nurani, 2019)
Karang Taruna is expected to be able to change the new order in the institutional dimension. Significant changes following the flow of globalization and decentralization turned out to bring new, more open challenges in the community. Changes also often arise in organizing organizations as is usual for an organization that indeed continues to demand improvements along with the changes in society that occur. The aim of this study was to find out the participation of the youth of Mahardika Youth Organization in the development of Jubel Kidul Village, Jubel Kidul Subdistrict, Lamongan Regency. This study uses a descriptive qualitative approach with in-depth interviews with 9 respondents, observing and investigating data using additional instruments such as interview guide lists, recorders and stationery. The results showed that the youth participation of the Mahardika Youth Organization in village development was demonstrated through activities carried out by Youth Youth, such as village clean-up activities, providing street lighting to the Village, streaking shock lines (sleeping police), social activities, activities commemoration of religious holidays and village consultation activities and consensus meetings. Keywords: Partisipasi Pemuda, Pembangunan Desa, Karang Taruna.